A highly efficient diode-pumped passively mode-locked Nd:Lu 1.5 Y 1.5 Al 5 O 12 laser - Di, J. Q. (2013)
In this letter, a diode-pumped passively mode-locked Nd:Lu1.5Y1.5Al5O12 (Nd:LuYAG) laser is demonstrated for the first time, to the best of our knowledge. With a semiconductor saturable-absorber mirror, a maximum output power of 0.85 W at 1064 nm was obtained under an absorbed power of 8.51 W, corresponding to a high slope efficiency of 44%. The mode-locked pulses were estimated to be 6.6 ps. The results of our experiment show that Nd:LuYAG crystal could be a promising material for diode-pumped ultra-short laser generation.